Observational study: effect of varying transport durations and feed withdrawal on the physiological status and health of dairy calves - Luca L. van Dijk; Susanne Siegmann; Niamh L. Field; Katie Sugrue; Cornelis G. van Reenen; Eddie A. M. Bokkers; Muireann Conneely; Gearoid Sayers (Irish Veterinary Journal)
Abstract Long-distance transport and associated fasting of unweaned calves have the potential to compromise the animals’ welfare. This observational study aimed to determine how transport and fasting durations impacted the physiology and health of 115 transported calves in three transport groups; IRE (n = 20, mean age 29.8d; short road transport (~ 29 h incl. resting time) and short feed deprivation (~ 11 h)), INT (n = 65, mean age 24.9d; long road/ferry transport (~ 79 h incl. resting times) and long feed deprivation (~ 28 h and 25 h)), and NLD (n = 30, mean age 17.7d; short road transport (~ 28 h incl. resting time) and long feed deprivation (> 18 h)). All calves travelled through an assembly centre. Each calf was blood sampled (arrival at destination farm, 1-week and 3-weeks post-arrival), health scored (arrival, 1, 3, 7, 8, 20d post-arrival) and weighed (farm/mart of origin [IRE and INT only], arrival, and 3-weeks post-arrival). (Generalised) linear mixed models were used to analyse differences in blood variables, weight, and health scores on arrival and during recovery (all other timepoints). Despite differing transport durations, both INT and NLD calves exhibited glucose, beta-hydroxy-butyrate, non-esterified-fatty-acids and sodium levels outside reference limits upon arrival, which were different from values observed in IRE calves (p < 0.05). Lactate and potassium were above reference range for INT calves on arrival, and higher than in IRE and NLD groups (p < 0.05). One- and three-weeks post arrival, most variables returned to within reference ranges, and differences between groups were minimal and not clearly associated with either transport duration or fasting during transport. Health scores did not differ between transport groups at arrival, and differences were minimal during the three-week recovery period. INT calves lost more weight during the journey than IRE calves (p < 0.01), while INT and NLD calves gained similar weight in the 3-weeks post-arrival, but less than IRE calves (both p < 0.01). Overall, changes in the physiological status of calves post transport appeared to relate more to the duration of feed deprivation than to the duration of transport, except for potassium and lactate (muscle fatigue), which were impacted more for INT calves. Most variables showed clear signs of recovery to within reference levels for all groups within three weeks. Minimizing the duration of feed deprivation during transport should be a key consideration for the dairy industry to reduce the impact of transport on calf welfare.